Decomposition rate of Quercus rotundifolia leaves in an evergreen oak forest of the Duero Basin (Province of Zamora, Spain) - HERNÁNDEZ, I; Gallardo, J F; Regina, I Santa; Quilchano, C (Plant Ecology, 1992)
Experimental litter decomposition of Quercus rotundifolia leaves in an evergreen oak forest of the semiarid area of the Duero Basin has been carried out. The loss of weight of the decomposing oak leaves was 623, j, after 24 months. In general, it is physical factors (mainly precipitation) which limit the decompo- sition of the evergreen oak leaves. Different patterns of bioelement losses were observed, increasing the relative content of N and P, and decreasing the amounts of Mg, K and Na in the decomposing leaves.
Keywords: forest ecosystems; leaf decomposition